Pleural effusions: role of commonly available investigations - How, Soon Hin; Chin, S P; Zal, A. R.; Liam, C K (Singapore Medical Association, 2006)
Malignancy is the commonest cause of pleural effusion, followed by tuberculosis and pneumonia, in patients treated in a teaching hospital in Malaysia. The number of undetermined causes could be minimised with a combination of readily-available and established investigations.